GPU Exploration of Two-Player Games with Perfect Hash Functions - Edelkamp, Stefan; Sulewski, Damian; Yücel, Cengizhan (Proceedings of the International Symposium on Combinatorial Search, 2010)
In this paper we improve solving two-player games by computing the game-theoretical value of every reachable state. A graphics processing unit located on the graphics card is used as a co-processor to accelerate the solution process. We exploit perfect hash functions to store the game states efficiently in memory and to transfer their ordinal representation between the host and the graphics card. As an application we validate Gasser's results that Nine-Men-Morris is a draw on a personal computer. Moreover, our solution is strong, while for the opening phase Gasser only provided a weak solution.